IMPLEMENTATION OF QUALITY ASSURANCE IN CURRICULUM STANDARDIZATION AND BENCHMARKING AT SPK SCHOOLS: A CASE STUDY OF CONTINUOUS QUALITY DEVELOPMENT AT KGS JAMBI - Mukhtar Latif; Jamrizal Jamrizal; Zulfa Rahmat Hidayati; Abdi Setiawan (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
This study examines the implementation of quality assurance in curriculum standardization and benchmarking at a Cooperation Education Unit School (SPK), with KGS Jambi serving as a single case. The research aims to analyse how internal quality assurance mechanisms, dual curriculum standardization, and systematic benchmarking practices are designed and implemented to support continuous quality improvement. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis involving school leaders, curriculum coordinators, senior teachers, and administrative staff. The findings show that KGS Jambi applies a comprehensive quality assurance system that aligns closely with Harvey and Green's five perspectives of educational quality, integrating national and international accreditation, performance monitoring, stakeholder evaluation, and alumni tracking. Curriculum standardization is carried out through the simultaneous adoption of the Merdeka Curriculum and the Cambridge Curriculum, supported by curriculum mapping, integrated syllabi, and regular curriculum reviews, thus balancing national values with global competitiveness. Benchmarking is implemented continuously through participation in SPK associations and the international Cambridge network, enabling the school to compare, adapt, and internalise best practices in management, curriculum, and assessment. The study concludes that KGS Jambi's model of quality assurance, curriculum standardization, and benchmarking offers a viable best-practice framework that can be adapted by Islamic educational institutions and other schools seeking to enhance their educational quality. It recommends the development of comprehensive quality assurance systems, structured curriculum standardization, and sustained benchmarking and networking as strategic pathways for continuous quality improvement in education